“Alexitimia y dependencia a la pasta base de cocaína en los pacientes del Centro Integral de tratamiento de adicciones Benito Menni, de Quito, periodo marzo-agosto 2016”. - Avalos Espinoza, Luis Enrique (2016)
This research has as its theme: Alexitimia and dependence cocaine paste in patients Comprehensive Addiction Treatment Center in Quito Benito Menni period March - August 2016. The objective was to determine the relationship between alexithymia and dependence cocaine base in patients CITABM-V paste. The research design was used in the field, documentary - bibliographical, descriptive type, the level of descriptive research. The study population was 22 males treated at the Center for Integrated Treatment of Addictions Benito Menni and the sample was selected based on the criteria of inclusion and exclusion, taking into account the validity of the test and applied survey, and considered 15 patients between 21 and 40 years. The instruments used were the scale LAC TAS-20 (LATIN AMERICAN CONSENSUS TORONTO alexithymia SCALE) that identifies the types of alexithymia and a survey to determine the dependence on cocaine base paste in which the diagnostic criteria for dependence are included under Manual CIE10, among the most significant results obtained from the application of psychological reagents was established that 47% of the total sample presents final alexithymia (equivalent to 7 people) and 100% of them have dependency to the base paste cocaine. With this base model to reduce psychological symptoms of alexithymia, which allow the person to be able to express, describe and distinguish between emotions and avoid relapse into the consumption of cocaine paste it was developed strategies.